Cartoons in scientific literacy: possibilities and alternative methodological tools in science and biology teaching (Research, Society and Development, 2020)
Scientific dissemination and popularization is an increasingly emerging need today. Amid so much incomplete or misleading information, providing reliable scientific information to the general population is fundamental to Science development. In this sense, cartoons are an interesting possibility for scientific dissemination and popularization, since not only children have access to such content, but also their carers. Thus, the present work analyzed three episodes of the “Show da Luna” cartoon. The analysis criteria were: concept, language and applicability in a school environment. It was found that the analyzed episodes don't show errors or conceptual distortions, as well as they use appropriate language for the audience for which they are intended. In addition, although it is a children cartoon, the episodes can be used as methodological tools in science and biology teaching.